PS1:18 Echocardiography for the assessment of cardiovascular burden in lupus: a single centre cohort study. (21st March 2018) - Ancuta, C; Pomirleanu, C; Paiu, R; Ancuta, E; Iordache, C; Chirieac, R; Mitu, F
Abstract : Despite major achievements in understanding the pathobiology and management of Systemic Lupus Erythematosus (SLE), cardio-vascular burden remains a complex challenge in routine practice. Echocardiography emerges as a valuable non-invasive technique widely recommended for the screening, evaluation and monitoring of cardiac involvement in different SLE settings. Objectives: to evaluate the prevalence and nature of the clinical and subclinical cardiac involvement in SLE, and to identify potential relation with several disease-related parameters. Design and methods: Retrospective observational study in 120 consecutive SLE (fulfilling either 1987 ACR or new 2012 SLICC/ACR criteria), mean age 36.9+15.2 years and mean disease duration 9.2+8.5 years, attending the outpatient rheumatology department at least once. Demographic, clinical, immunologic profile, disease activity (SLEDAI), organ damage (SLICC/ACR) data were collected. Patients were assessed according to a standardised protocol focused on clinical, immunologic profile, disease activity (SLEDAI), severity and organ damage (SLICC/ACR); cardiac involvement (valve damage, systolic and diastolic dysfunction, pericardial disease, myocardial ischemia, pulmonary hypertension) was evaluated by 2D transthoracic echocardiography (TTE). Statistical analysis was done in SPSS, p<0.05. Results: Valvular disease was reported in 61.98% SLE (14% stenosis, 20.66% valvular masses, 33% mild-to- moderate regurgitation, 34.73% leaflet thickening. Libman-Sacks endocarditis was not depicted. Asymptomatic decrease in left ventricular ejection fraction (55%) was described in 16.52%, the lowest LVEF being 33% in 4.13% patients; statistical significant negative correlation LVEF – disease duration and activity (p<0.05) was found. LV diastolic dysfunction as subclinical cardiac involvement was registered in 59.50% SLE, with a direct correlation with disease duration (p<0.05), but not with disease activity (SLEDAI) and organ damage (SLIC/ACR) (p>0.05). Global hypokinesis on TTE as an indicator of subclincal myocarditis was demonstrated in up to one third SLE, while cardiomyopathy in one fourth. Mild pericardial effusion is observed in 31.2% cases, while cardiac tamponade in 4 cases; pericardial thickening was reported in 38% SLE. Finally, abnormal systolic pressure in pulmonary artery was found in 24.79% patients. Conclusion: Patients with SLE are at increased risk to develop either clinical or subclinical cardiovascular manifestations as demonstrated by echocardiographic studies. A systematic TTE assessment is routinely recommended for the screening and monitoring of cardiac events.